A differential game with timing - Jačiauskas, I. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. П. Ячяускас. Одна дифференциальная игра с выбором момента времени I. Jačiauskas. Vienas diferencialinis lošimas su laiko momento parinkimu